Understanding the Unmet Needs of Epilepsy in Indian population - Rajesh Pandita (Function and Disability Journal, 2025)
Background and Objectives: Epilepsy, a neurological disorder, affects approximately 50 million individuals worldwide, including around 12 million in India. Inadequate treatment of epilepsy can significantly impact daily routines and compromise both the physical and mental health of affected individuals. This article aims to investigate whether the Indian population possesses a fundamental understanding of epilepsy to evaluate the level of awareness and comprehension among the public and explore the reasons why patients may still resort to sorcery. Methods: To assess epilepsy knowledge among the urban population in India, a quantitative research approach utilizing structured closed and open-ended questionnaires and a thorough review of existing literature was employed. Of the 418 individuals approached, 401 participated in the study, and their responses were analyzed statistically. Results: Preliminary results indicated a broad spectrum of awareness levels in the Indian population. While some demonstrated an adequate understanding of epilepsy, others still harbour misconceptions and erroneous beliefs. Factors, such as socioeconomic status, education level, cultural influences, and access to accurate information may influence these variations in understanding. 26% of responders said that epilepsy is contagious, the prevalence of epilepsy was 56% among responders, 31% still resort to sorcery, 38% think that an epileptic person cannot get married, and 10% believe that letting a patient during seizures smell socks or onion will help instead to seek proper medical treatment. Conclusion: The compelling results indicate the need for public health campaigns, educational initiatives, and awareness programs to bridge informational gaps and improve the quality of life (QoL) for people with epilepsy (PWE). Epilepsy disrupts the daily lives of patients, emphasizing the critical need for community education on the condition in India. Further research in rural areas is essential to gain a deeper understanding of public perceptions of epilepsy and its impact on those living with the disorder.